If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(14) + u + -40 = 19u + 14 Multiply 9 * 14 126 + u + -40 = 19u + 14 Reorder the terms: 126 + -40 + u = 19u + 14 Combine like terms: 126 + -40 = 86 86 + u = 19u + 14 Reorder the terms: 86 + u = 14 + 19u Solving 86 + u = 14 + 19u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-19u' to each side of the equation. 86 + u + -19u = 14 + 19u + -19u Combine like terms: u + -19u = -18u 86 + -18u = 14 + 19u + -19u Combine like terms: 19u + -19u = 0 86 + -18u = 14 + 0 86 + -18u = 14 Add '-86' to each side of the equation. 86 + -86 + -18u = 14 + -86 Combine like terms: 86 + -86 = 0 0 + -18u = 14 + -86 -18u = 14 + -86 Combine like terms: 14 + -86 = -72 -18u = -72 Divide each side by '-18'. u = 4 Simplifying u = 4
| 12/9=4/× | | f(x)=x^3-3x^2+4x+1 | | 72/8-3= | | 2[p-(2p+13)+8]=2(p+5) | | (5+3)x(10-6)= | | -5+9-24=x | | ×-5/4=(-7) | | x^2+(2-k)x+k=0 | | 17+3z=-3 | | (3x+7)+(2x+19)+3x=180 | | (3x+7)+(2x+19)+x=180 | | (3x+7)+(2x-19)+3x=180 | | 47618.52=x-.05x | | 3x-5(-3)=15 | | 13y^2+32y-8=0 | | 3+log[5](-5x)=5 | | 4-3(x-2)=28 | | ln*(x+7)+ln*9=2 | | 5f=-14+3f | | -4d-18=-2d+12 | | 8+20p=-9+19p+5 | | lg(x-8)=2-lgx | | 60-10y=30 | | 27xy-63x-21y+49= | | 5+6q=-5+5q | | 5a+15b=300 | | tg(x)*(sin(x)+cos(x))=0 | | 20x^2-8xy+5x-2y= | | 7j=3+4j | | cos(x)+cos(2*x)+cos(3*x)=0 | | (n-3)=(n-5) | | 16x^2-72xy+2x-9y= |